DEVELOPMENT OF ANIMATED FILM MEDIA TO INCREASE STUDENT CONFIDENCE SMP NEGERI 3 PRAMBANAN YOGYAKARTA - Nurul Insani; Muhammad Nur Wangid (SOSIOEDUKASI, 2026)
Development of Animated Film Media to Increase Self- Confidence of Students at Prambanan 3 Junior High School, Yogyakarta. Thesis. Yogyakarta: Faculty of Education, Yogyakarta State University, 2025.This research aims to produce animated film media that: (1) meets eligibility criteria, (2) is practical, and (3) is effective for use in guidance and counseling services to increase student self-confidence. The research and development method used was the ADDIE model, adapted from the Branch development model. The research stages included analysis, design, development, implementation, and evaluation. The research was conducted at Prambanan 3 Junior High School Yogyakarta. The trial subjects were 92 students, consisting of two experimental classes and one control class. Data collection techniques included observation, questionnaires, and a self-confidence scale. Data were analyzed using qualitative and quantitative approaches. The results indicate that: (1) the animated film media is declared highly feasible by media experts and material experts based on validation results; (2) the media meets practicality criteria, with an average score of 3.64 from teachers and a score of 91 from students, both of which fall into the very practical category; and (3) the media effectively increases student self-confidence. The effectiveness is proven through the N-gain calculation, which shows an increase in self-confidence scores in the experimental class higher than the control class. The ANOVA test using SPSS produces an F value of 16.316 with a significance of 0.000 (p < 0.05), so H0 is rejected. This indicates that animated film media has a significant effect on increasing the self-confidence of junior high school students.